Cover Image, Volume 140, Issue 9. Issue 9 (22nd January 2023) - Sudprasert, Pirada; Kariya, Shotaro; Ogino, Kenji; Chirachanchai, Suwabun; Kanehashi, Shinji
Abstract : The cover designed by Shinji Kanehashi presents the development of novel bio‐based polymers derived from the shell liquid of cashew nuts, which is a phenolic compound in non‐edible plant oil obtained from cashew nut shells. The epoxy polymer was prepared from cardanol derivatives, epoxy prepolymer and phenalkamine at room temperature without solvent. This epoxy polymer possessed anti‐microbial activity against E.coli and S. aureus . The mechanical and thermal properties of this epoxy polymer were improved effectively by a post‐curing process. DOI: 10.1002/app.53450